The Influence of Learning Performance on Islamic Religious Education on Student Behavior at SMP 1 Montasik - Marlina , Leni (MANDAILING GLOBAL EDUKASIA, 2024)
The purpose of this research is to find out if there is an influence on the learning performance of Islamic Religious Education on the behavior of SMP Negeri 01 students Montasik. The research method used in this research is quantitative research with a descriptive approach. The population in this research is 451 students of SMP Negeri 01 Montasik. While the sample of this research is 45 grade VIII students. Data collection techniques for this research use questionnaires, observations and documentation. The results of the research revealed that among the learning performance variables of Islamic religious education, the behavior of students has a significant positive influence with a significant value of 0.533 greater than 0.05. The value of Fhitung is 0.904 while the value of Ftabel with df 9.34 in the distribution table with the value of F0.05 is Ftabel = 2.17, because the value of Fhitung is smaller than Ftabel (Fhitung < Ftabel or 0.904 < 2.17) it is concluded that there is a significantly linear relationship. This means that there is a significant influence between the learning performance variable of Islamic religious education (X) and the behavioral variable of SMP Negeri 01 Montasik (Y) amounting to 93.7% while the remaining 6.3% is influenced by other variables.